Different tracks : the Agapitos/Wilson collection of contemporary Aboriginal art. - Maitland Regional Art Gallery (Maitland, N.S.W. : Maitland Regional Art Gallery, 2009)
Exhibition catalogue of works from the collection of James Agapitos and Ray Wilson on contemporary Aboriginal art, includes an essay on the background to the collection; features works by Pantjiti Mary McLean, Ningura Napurrula, George Tjampu Tjapaltjarri, Patrick Tjungurrayi, Yala Yala Gibbs Tjungurrayi, Ronnie Tjampitjinpa, Walangkura Napanangka, Naata Nungurrayi, Tjunkiya Napaltjarri, Freddy Timms, John Mawurndjul, Samuel Namunjdja, George Ward Tjungurrayi, Ray James Tjangala, Lorna Brown Napanangka, Jean Baptiste Apuatimi, Pedro Wonaeamirri.
Catalog of an exhibition held at the Maitland Regional Art Gallery, 15 August - 22 November 2009.
Keywords: Agapitos, James -- Art collections -- Exhibitions; Wilson, Ray -- Art collections -- Exhibitions; Art, Aboriginal Australian -- Exhibitions; Art - Artists; Art - Exhibitions; Art - Collections; Art - Collections - Collectors